2021
DOI: 10.3389/fenvs.2021.724702
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis Approach to Measure the Effect of Integrated Nutrient Management on Crop Performance, Microbial Activity, and Carbon Stocks in Indian Soils

Abstract: Cereal crop production gains under conventional agricultural systems in India have been declining in recent years because of inadequate management practices, creating a considerable concern. These activities were shown to deplete soil organic matter stocks, resulting in a decrease in microbial activity and soil organic carbon (SOC) content. Moreover, even with minimal use of organic sources in cultivated land, soil carbon status deteriorated, particularly in subtropical climates. Integrated nutrient management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 95 publications
1
7
0
Order By: Relevance
“…The MQ value can also reflect about the quality and nature of microbial activity in the soil. A large number of studies on MQ have shown its importance to evaluate or monitor the influence of short-or long-term changes in soil biological status due to management and other system-level manipulations (Brookes, 1995;Bastida et al, 2008;Anderson and Domsch, 2010;Padbhushan et al, 2021). Soil properties and SOC stocks may be altered due to soil disturbances (Guo and Gifford, 2002;Paul et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The MQ value can also reflect about the quality and nature of microbial activity in the soil. A large number of studies on MQ have shown its importance to evaluate or monitor the influence of short-or long-term changes in soil biological status due to management and other system-level manipulations (Brookes, 1995;Bastida et al, 2008;Anderson and Domsch, 2010;Padbhushan et al, 2021). Soil properties and SOC stocks may be altered due to soil disturbances (Guo and Gifford, 2002;Paul et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, sole usage of organic inputs and mineral fertilizers are not sufficient to cover the gap between mineral deficiency and the requirement of grain crops. Thus, the combination of both interventions is effective as they have positive interactions and complementary functions [72].…”
Section: Biofortification Through Agronomic Management Practicesmentioning
confidence: 99%
“…Rice yield improved in RDF plots and they improved more when organic sources were substituted (Padbhushan et al, 2021;Singh et al, 2018). Sowmya et al (2011) also stated that integrated nutrient management, is necessary for long-term output.…”
Section: Grain and Straw Yieldmentioning
confidence: 99%